Preparation of an Fe2Ni MOF on nickel foam as an efficient and stable electrocatalyst for the oxygen evolution reaction. Issue 57 (18th October 2019) - Ling, Xintong; Du, Feng; Zhang, Yintong; Shen, Yan; Li, Tao; Alsaedi, Ahmed; Hayat, Tasawar; Zhou, Yong; Zou, Zhigang
Abstract : Fe2 Ni-MIL-88B MOF on nickel foam (Fe2 Ni MOF/NF) has excellent OER performance through a one-pot method. Abstract : Metal–organic frameworks (MOFs) as versatile templates for preparing transition metal compounds has received wide attention. Benefiting from their diversified spatial structure and controllable chemical constituents, they have become a research hotspot in the field of electrocatalytic water splitting. Herein, Fe2 Ni-MIL-88B MOF on nickel foam (Fe2 Ni MOF/NF) has been prepared through a one-pot method growth process. Compared with Fe MOF/NF and Ni MOF/NF, the interaction between Fe 3+ and Ni 2+ in Fe2 Ni MOF/NF accelerates the electron transfer through the oxygen of the ligand, leading to increased 3d orbital electron density of Ni, which enhances the activity of the oxygen evolution reaction (OER) in alkaline solution. Fe2 Ni MOF/NF provides a current density of 10 mA cm −2 at a low overpotential of 222 mV, and its Tafel slope is also very small, reaching 42.39 mV dec −1 . The success of the present Fe2 Ni MOF/NF catalyst is attributed to the abundant active centers, the bimetallic clusters Fe2 Ni-MIL-88B, the positive coupling effect between Ni and Fe metal ions in the MOF, and synergistic effect between the MOF and NF. Besides, Fe2 Ni MOF/NF possesses excellent stability over 50 h of continuous operation, providing feasibility for commercial use.